2018
DOI: 10.1016/j.jnucmat.2017.11.041
|View full text |Cite
|
Sign up to set email alerts
|

The fractalline properties of experimentally simulated PWR fuel crud

Abstract: The buildup of fouling deposits on nuclear fuel rods, known as crud, continues to challenge the worldwide fleet of light water reactors (LWRs). Crud may cause serious operational problems for LWRs, including axial power shifts, accelerated fuel clad corrosion, increased primary circuit radiation dose rates, and in some instances has led directly to fuel failure. Numerous studies continue to attempt to model and predict the effects of crud, but each makes critical assumptions regarding how to treat the complex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Upon the recent years, researchers have built upon this concept and developed it into different crud calculation models [5][6][7][8][9][10][11]. In the experimental research, scientists observed the fractalline properties of PWR fuel crud [12] and then found that a systematic theory of fractal porous media [13] can be used to refine some parameters and assumptions in the crud model.…”
Section: Introductionmentioning
confidence: 99%
“…Upon the recent years, researchers have built upon this concept and developed it into different crud calculation models [5][6][7][8][9][10][11]. In the experimental research, scientists observed the fractalline properties of PWR fuel crud [12] and then found that a systematic theory of fractal porous media [13] can be used to refine some parameters and assumptions in the crud model.…”
Section: Introductionmentioning
confidence: 99%